Minecraft atlas of the world - Jelley, Craig (DK Publishing, 2025)
This illustrated children's book introduces real-world geography, wildlife, and notable landmarks through Minecraft-style builds and explanations. Combining factual information about global locations with creative building ideas, the book offers readers an overview of continents, natural wonders, plants, animals, and historic structures, along with tips for recreating these features within the Minecraft game.